Coupled PD-SPH modeling for fluid-structure interaction problems with large deformation and fracturing. (1st October 2022) - Yao, Xuehao; Huang, Dan
Highlights: A novel SPH-PD coupling strategy for FSI induced structure failure. Non-slip solid-fulid boundary condition can be easily implemented. Handling FSI problems with large deformation of structure and fracture. Simulation of solid fragmentation under water jet. Abstract: A simple and accurate coupled peridynamics (PD) and smoothed particle hydrodynamics (SPH) strategy based on virtual particles and repulsive forces is proposed to simulate fluid-structure interaction (FSI) problems with large deformation and fracturing. In the coupling framework, SPH method is employed to model fluid domain, and peridynamic theory is applied to describe the deformation and fracture of structure. To deal with the fluid-structure interfacial region, the peridynamic particles within the support domain of fluid particles are treated as virtual particles through which full kernel support of fluid particles are ensured, different boundary conditions on fluid particles can be imposed and repulsive forces preventing penetration are exerted. For momentum conservation, peridynamic particles acting forces on fluid particles are simultaneously subjected to opposite forces. Validation studies for the peridynamic model of pure solid structure and the coupled PD-SPH model of FSI involving large deformation and fracture have been performed, all presenting close agreement with analytical solutions, available experimental data, and/or other numerical results. Finally, the proposed approach is employed to study water-jetting rock fragmentation problems and the results further demonstrate that the proposed coupled PD-SPH model is capable of handling complex FSI problems with fluid-induced solid breaking.